COMMUNITY STRUCTURE OF MACROALGAE IN LEMUKUTAN ISLAND WATERS, WEST KALIMANTAN - Safitri, Ikha; Juane, Mega Sari; Warsidah, Warsidah; Helena, Shifa; Minsas, Sukal; Yuliono, Agus (Jurnal Ilmu Kelautan SPERMONDE, 2022)
Macroalgae or known as seaweed is one of the potential resources and is responsible for primary productivity in marine waters. Macroalgae plays an important role in marine ecosystems, provides food, oxygen, and habitat for several types of marine biota. Moreover, macroalgae have been reported as renewable resources in marine environment and widely used in various fields. The biodiversity and abundance of macroalgae are strongly influenced by aquatic environmental factors. Lemukutan Island is the largest inhabited island located in Bengkayang Regency, West Kalimantan and has the potential natural resources, including macroalgae. This Island can become a center for producing macroalgae that can be used to meet food needs both locally and domestically. The main objective of this study were to determine the community structure of macroalgae and the condition of the environmental physico-chemical parameters. The sampling locations were carried out in-situ at three stations and the determination of the sampling site was done by purposive random sampling method, by selecting an area based on the presence of macroalgae. The sampling of macroalgae was carried out using a quadratic transect with size of 10x10 m2 and the water quality parameters were measured using the AZ 8603 of WQC instrument. The study found 6 genera of macroalgae, such as Caulerpa, Halimeda, Padina, Turbinaria, Sargassum, and Gracillaria. Among the identified macroalgae, Phaeophyceae have the highest per cent contribution (50%), and Padina had the highest abundance (29.84 ind/m2). Lemukutan Island waters had a moderate level of diversity, high macroalgae uniformity, and dominance index in the low category. The aquaatic environmental factors influenced the abundance of macroalgae in Lemukutan Island waters.